2013
DOI: 10.4161/chan.26789
|View full text |Cite
|
Sign up to set email alerts
|

Divalent regulation and intersubunit interactions of human Connexin26 (Cx26) hemichannels

Abstract: Control of plasma membrane connexin hemichannel opening is indispensable, and is achieved by physiological extracellular divalent ion concentrations. Here, we explore the differences between regulation by Ca(2+) and Mg(2+) of human connexin26 (hCx26) hemichannels and the role of a specific interaction in regulation by Ca (2+). To effect hemichannel closure, the apparent affinity of Ca(2+) (0.33 mM) is higher than for Mg(2+) (1.8 mM). Hemichannel closure is accelerated by physiological Ca(2+) concentrations, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 9 publications
4
33
0
Order By: Relevance
“…Only a few point mutations led to functional hemichannels (D46C, E47Q, D50N, R184K), but all showed accelerated deactivation kinetics at all extracellular Ca 2+ concentrations. We previously showed that Cx26 hemichannels deactivate very slowly at low extracellular Ca 2+ because the electrostatic interaction between D50 and K61 is less likely to be disrupted, which stabilizes the hemichannel in the open state (17,19). Charge-changing mutations of these residues that weaken the interaction accelerate the closing kinetics (17,19), similar to results seen with D46C, E47Q, and R184K mutant hemichannels.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Only a few point mutations led to functional hemichannels (D46C, E47Q, D50N, R184K), but all showed accelerated deactivation kinetics at all extracellular Ca 2+ concentrations. We previously showed that Cx26 hemichannels deactivate very slowly at low extracellular Ca 2+ because the electrostatic interaction between D50 and K61 is less likely to be disrupted, which stabilizes the hemichannel in the open state (17,19). Charge-changing mutations of these residues that weaken the interaction accelerate the closing kinetics (17,19), similar to results seen with D46C, E47Q, and R184K mutant hemichannels.…”
Section: Discussionsupporting
confidence: 66%
“…We previously showed that Cx26 hemichannels deactivate very slowly at low extracellular Ca 2+ because the electrostatic interaction between D50 and K61 is less likely to be disrupted, which stabilizes the hemichannel in the open state (17,19). Charge-changing mutations of these residues that weaken the interaction accelerate the closing kinetics (17,19), similar to results seen with D46C, E47Q, and R184K mutant hemichannels. In addition, in steady-state measurements, mutations of D50 and E47 significantly reduce the apparent affinity for Ca 2+ , suggesting that they also reduce the ability of Ca 2+ to stabilize the closed state.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Xenopus oocytes were injected with the same amount of Cx45 WT or 6E cRNA, together with DNA antisense to the endogenous XenCx38. The oocytes were voltage-clamped and macroscopic currents of the hemichannels recorded during steps to depolarizing voltages to activate the channels [44, 45] (Fig. 8).…”
Section: Resultsmentioning
confidence: 99%